Winter North Atlantic Oscillation hindcast skill: 1900-2001 - Fletcher, CG; Saunders, MA (AMER METEOROLOGICAL SOC, 2006)
Recent proposed seasonal hindcast skill estimates for the winter North Atlantic Oscillation (NAO) are derived from different lagged predictors, NAO indices, skill assessment periods, and skill validation methodologies. This creates confusion concerning what is the best-lagged predictor of the winter NAO. To rectify this situation, a standardized comparison of NAO cross-validated hindcast skill is performed against three NAO indices over three extended periods (1900-2001, 1950-2001, and 1972-2001). The lagged predictors comprise four previously published predictors involving anomalies in North Atlantic sea surface temperature (SST), Northern Hemisphere (NH) snow cover, and an additional predictor, an index of NH subpolar summer air temperature (T-SP). Significant (p < 0.05) NAO hindcast skill is found with May SST 1900-2001, summer/autumn SST 1950-2001, and warm season snow cover 1972-2001. However, the highest and most significant hindcast skill for all periods and all NAO indices is achieved with T-SP. Hindcast skill is nonstationary using all predictors and is highest during 1972-2001 with a T-SP correlation skill of 0.59 and a mean-squared skill score of 35%. Observational evidence is presented to support a dynamical link between summer T-SP and the winter NAO. Summer T-SP is associated with a contemporaneous midlatitude zonal wind anomaly. This leads a pattern of North Atlantic SST that persists through autumn. Autumn SSTs may force a direct thermal NAO response or initiate a response via a third variable. These findings suggest that the NH subpolar regions may provide additional winter NAO lagged predictability alongside the midlatitudes and the Tropics.